Failure Of Second Line ART Demands Third -Line Options For HIV-Infected Patients In Telangana, India - g, krishna; Pandharpurkar, Deepak; Mallikarjun, P. (Clinical and Research Journal in Internal Medicine, 2024)
Back ground: The research was carried out with the aim of detecting instances of second-line antiretroviral therapy (ART) failure and exploring the potential of third-line ART treatment for individuals with HIV, incorporating the utilization of HIV viral load (VL) testing. Beginning in 2016-17, individuals living with HIV are directed to government ART centers and ART plus centers for treatment. Patients who have experienced treatment failure with second-line therapy and have been exposed to multiple NRTIs, in accordance with the Indian National ART Guidelines, are referred to the SACEP Clinic for further evaluation. If deemed eligible according to the Indian National 3rd Line ART Guidelines, these patients are enrolled and followed up for the initiation of 3rd Line ART at our center. Throughout the duration of the study, a collective of 55 individuals diagnosed with Human Immunodeficiency Virus (HIV) were identified as potentially experiencing a lack of efficacy with regards to their secondary line antiretroviral therapy (ART). Two patients in the cohort were diagnosed with both HIV and multi drug resistant tuberculosis (MDR-TB). Method: Fifty-four and a half percent of the patient sample was classified as being in WHO stage I, while 32.8% were categorized as being in stage II, and the remaining 12.7% were identified as being in WHO stage IV. Fifty-five patients who were suspected of experiencing second-line treatment failure were transitioned to third-line antiretroviral therapy. Results: All 55 patients underwent VL follow-up, with 53 of them attaining viral suppression within a median period of 6 months. However, two patients were unable to achieve viral suppression. Conclusion: However, this study describes HIV-positive patients who need third-line ART due to probable second-line ART failure.